Direct-Write Printed Slippery Surface for Assembling a High-Quality Graphene Structure and Its Application in Flexible Electric Actuators - Kang, Haiting (Langmuir : the ACS journal of surfaces and colloids, 2024)
Graphene is a two-dimensional honeycomb-like nanomaterial generated by carbon atoms in sp2 hybridized orbitals to form a hexagonal lattice structure with excellent electrical, optical, and mechanical properties. The solution process method has been widely used to realize large-area patterned graphene structures for high-performance devices. In the method, graphene usually needs to be dispersed in solution, and the π-π bonding gravitational interactions between graphene sheets would lead to uncontrollable structures in solution and difficulty in obtaining high performance. In this work, a patterned graphene oxide (GO) structure with controllable thickness and layer spacing was realized by a direct-write printed slippery surface, which was used as a slippery limited template. After reducing GO into reduced graphene oxide (rGO), a flexible electric pattern with a conductivity of up to 6.425 × 103 S/m was realized. Furthermore, the patterned rGO structure was transferred on polydimethylsiloxane (PDMS), which could generate less than a 5% change in resistance after 10,000 consecutive bends, and an anisotropic expansion based on rGO and PDMS materials under electro-thermal coupling. The patterned rGO structures could meet the performance requirements of highly sensitive and complex deformation applications as flexible electric actuators. This study provides great research significance and application value for patterning high-quality graphene structures and realizing high-performance flexible electronic devices